Are early life factors considered when managing respiratory disease? A British Thoracic Society survey of current practice. Issue 12 (19th September 2012) - Bolton, Charlotte E; Bush, Andrew; Hurst, John R; Kotecha, Sailesh; McGarvey, Lorcan; Stocks, Janet; Walshaw, Martin J
Abstract : ABSTRACT: Background: We hypothesised that early life events are not routinely considered by most respiratory specialists. Methods: Respiratory Specialists were surveyed via the British Thoracic Society (BTS) on whether they asked patients about birth weight, preterm birth and prenatal and postnatal complications. Results: Only a small minority (mostly hospital paediatricians) of the 123 who replied asked most respiratory patients about one of more early life factors. Patient recall of the information when asked was low. Conclusions: The survey results suggest little current consideration is given to early life factors in adult respiratory medicine, despite increasing evidence that early life factors do impact on later respiratory health. Improving training, increasing awareness and exploring new approaches to obtaining the information are required.